Penerapan Media Pembelajaran Berbasis Poster Pada Materi Teks Eksposisi Untuk Meningkatkan Prestasi Belajar Bahasa Indonesia Pada Siswa Kelas X Smk Negeri Noebaun Kecamatan Oenino Kabupaten Timor Tengah Selatan Tahun Ajaran 2025/2026 - Afna Katarina Sayuna; Ronni M. Ndun; Arnol Kolnel (JURNAL ILMIAH NUSANTARA, 2026)
The problem addressed in this study is whether the implementation of poster-based learning media for exposition text material can improve the learning achievement of Grade X students at SMK Negeri Noebaun. The study aims to determine the improvement in student learning achievement resulting from the use of poster learning media. The theoretical framework covers learning media, poster-based learning media, and learning achievement. The research employs Classroom Action Research (CAR) methodology, proceeding through the stages of planning, implementation, and reflection. Data collection involved 26 Grade X students at SMK Negeri Noebaun using observation, testing, and documentation techniques. Data analysis utilized both quantitative and qualitative methods; students' exposition texts were evaluated based on three aspects—text structure, cohesion and coherence, and linguistic rules—using a scale of 1 to 4, where 1 represents the lowest category and 4 the highest. The results show that in Cycle I, 8 out of 26 students (30.76%) achieved mastery, demonstrating the ability to write effectively, while 18 students (69.23%) did not achieve mastery, as their writing was not yet proficient and required further guidance. In Cycle II, 17 students (65.38%) achieved mastery, successfully writing poster-based exposition texts, while 9 students (34.62%) did not achieve mastery, as they still required guidance to write effectively. Comparison of the Cycle I and Cycle II test results indicates an increase in the average class score, and the learning mastery rate rose to 100%. Thus, the study demonstrates that the implementation of poster-based learning media for exposition text material can improve student learning achievement.